Infant and young child feeding practices among tribal mothers in Sambalpur district, Odisha, India - Sahu, Samyak; Pradhan, Subrat K.; Panda, Sadhu C. (International Journal Of Community Medicine And Public Health, 2020)
Background: Indicators of infant and young child and feeding (IYCF) practices have been devised by WHO in order to help objectively assess the prevalence of these practices in the population. IYCF practices play a vital role in the control of infant and child deaths. This study was undertaken to assess the IYCF practices among children aged less than 2 years among the tribal population. Objective of this study to measure the indicators of IYCF practices in children in the 0-23 months age group. Methods: It is a community based, cross sectional study of infant and young child feeding practices among tribal mothers having children younger than 24 months, in Sambalpur district of Odisha from October 2017 to December 2019. The study participants were tribal mothers having children less than 24 months of age. The sample size was 384. Results: Among the study participants, 93.5% belonged to the 21-30 years age bracket, 37.5% had middle school certificate education and 75.3% belonged to the upper lower socioeconomic class. The indicators were continued breastfeeding at 1 year (100%), continued breastfeeding at 2 years (100%) and children ever breastfed (100%), exclusive breastfeeding (98.71%) and bottle feeding (16.36%). A significant association was found between delivery by lower segment caesarean section and delayed initiation of breastfeeding. Conclusions: The indicators related to breastfeeding and complementary feeding were adequate except for minimum dietary diversity and minimum adequate diet.